Difusi dan Pola Spasial Sebaran Penyakit Demam Berdarah Dengue (DBD) Di Kota Bandar Lampung - Qamila, Nurul; Krama, Agel Vidian (KESMARS: Jurnal Kesehatan Masyarakat, Manajemen dan Administrasi Rumah Sakit, 2018)
Dengue hemorrhagic fever (DHF) is a contagious disease caused by the dengue virus and is transmitted by the mosquito Aedes aegypti (Aa.aegypti). The population is still a public health problem that increases the number of sufferers and also widespread, with population and education. This study aims to reveal the spatial pattern and distribution of Dengue Hemorrhagic Fever (DHF) with the spatial pattern and the spread of Dengue Hemorrhagic Fever (DHF) can result in different locations of these allegations. From the map that can be used for the prevention of Dengue Hemorrhagic Fever (DBD) in Bandar Lampung City. This study aims to reveal the spatial pattern and distribution of Dengue Hemorrhagic Fever (DHF) with the descriptive method and spatial pattern of Dengue Hemorrhagic Fever (DHF) can result in different locations of these allegations. From the map that can be used for the prevention of Dengue Hemorrhagic Fever (DBD) in Bandar Lampung City. Keywords: DHF, Spatial Analysis